Gamification Design to Increase Motivation in Online Learning Environments: A Systematic Review - Kübra ERTAN; Selay ARKÜN KOCADERE (Journal of Learning and Teaching in Digital Age, 2022)
Lack of learner motivation is one of the problems that can be encountered in online learning settings. Gamification can be offered as a possible solution to the motivational problems in online learning environments. In this regard, this study aims to give a general idea of gamification studies focusing on motivation in online learning and to provide practical suggestions on designing gamification. In order to access relevant studies, Web of Science Core Collection database was reviewed. In total, 90 articles in SSCI index journals have been systematically analyzed and 10 of them meeting the inclusion criteria were reviewed in detail. While one of those studies revealed no significant effect of gamification on motivation, the rest of them showed that gamification is effective in fostering students’ motivation. This review provides a general overview about the effect of gamification on motivation and suggestions for future implications such as including badges or points to show competence, using competitive and collaborative elements together, preparing different types of leaderboards, providing students with immediate and automated feedback, giving students challenges suitable for their skills, developing adaptive gamification systems for different learner needs, and eliminating technical problems.